Pulse Interval Modulation for Ultra-High Speed IR-UWB Communications Systems. (5th August 2010) - Herceg Herceg, Marijan Marijan; Švedek Švedek, Tomislav Tomislav; Matić Matić, Tomislav Tomislav
Abstract : This paper analyzes performances of the Pulse Interval Modulation (PIM) scheme for impulse radio ultra-wideband (IR-UWB) communication systems. Due to the PIM anisochronous nature, a tap delay line (TDL) coded division multiple access (CDMA) scheme based on strict optical orthogonal codes (SOOC) is proposed. This scheme is suitable for multiuser high-speed data asynchronous transmission applications because the average symbol length is shorter than in Pulse Position Modulation (PPM) schemes and it needs only chip synchronization. The error probability over the additive white Gaussian noise (AWGN) channel is derived in the single- and multi-user environment and compared with other modulation schemes.